Sensitivity Analysis Of Business Feasibility Using Palm Kernel Cake (PKC) Solid Waste In Composing Of Palm Oil Leaf - Dina Arfianti Saragih; Ingrid Ovie Yosephine; M. Zulhamsyah Nst (JASc (Journal of Agribusiness Sciences), 2021)
Palm leaf fronds have the potential to be used as compost material. The utilization of palm oil used as compost stems from the large number of palm oil leaves that are discarded when harvesting is not used. Moreover, in the palm oil company, after harvesting the leaves of the palm oil, it is only thrown away that is increasingly piled up on company land. Based on this, a research on adding Palm Kernel Cake (PKC) solid waste for the composting process can accelerate the decomposition process and as a food enhancer in the composting process. This is also carried out a business feasibility sensitivity analysis to determine whether a business is feasible in composting oil palm fronds with an increase in price of 1-10%. The research was conducted This research was carried out in the greenhouse of the Agricultural Agribusiness College of Agriculture (STIPAP) Medan in April to June 2019. This research used a descriptive design that explains the process flow of the cost component of the feasibility of the business feasibility of making oil palm frond compost using solid waste Palm Kernel Cake. The results showed that the business of making oil palm frond compost using Palm Kernel Cake benefited from a 1-10% price increase of Rp. 613,117-Rp. 489,534 and was still feasible to run with a total production cost of a 1-10% increase in the amount of Rp. 1,386,883- IDR 1,510,466. R / C Ratio 1.44-1.34 from 1-10% increase is feasible to run because R / C Ratio 1 and B / C Ratio value 0.44-0.34 is not feasible to run because B / C Ratio 1.